Lidar mapping of atmospheric atomic mercury in the Wanshan area, China. (September 2018) - Lian, Ming; Shang, Lihai; Duan, Zheng; Li, Yiyun; Zhao, Guangyu; Zhu, Shiming; Qiu, Guangle; Meng, Bo; Sommar, Jonas; Feng, Xinbin; Svanberg, Sune
Abstract: A novel mobile laser radar system was used for mapping gaseous atomic mercury (Hg 0 ) atmospheric pollution in the Wanshan district, south of Tongren City, Guizhou Province, China. This area is heavily impacted by legacy mercury from now abandoned mining activities. Differential absorption lidar measurements were supplemented by localized point monitoring using a Lumex RA-915M Zeeman modulation mercury analyzer. Range-resolved concentration measurements in different directions were performed. Concentrations in the lower atmospheric layers often exceeded levels of 100 ng/m 3 for March conditions with temperature ranging from 5 °C to 20 °C. A flux measurement of Hg 0 over a vertical cross section of 0.12 km 2 resulted in about 29 g/h. Vertical lidar sounding at night revealed quickly falling Hg 0 concentrations with height. This is the first lidar mapping demonstration in a heavily mercury-polluted area in China, illustrating the lidar potential in complementing point monitors. Graphical abstract: Image 1 Highlights: Differential absorption lidar was shown effective in Hg 0 monitoring. Intercomparison with standard device shows good agreement. Relics of ancient mines served as major sources of local mercury pollution. Extremely high atomic mercury concentrations, up to 200 ng/m 3, were observed. A flux measurement gave a result of 29 g/h within a 0.12 km 2 vertical cross section.